Assessment and validation of three spot urine assay methods for the estimation of 24‐hour urinary sodium excretion in Chinese Tibetan adults living in the mountains. Issue 8 (1st July 2021) - Zhang, Xin; Liao, Hang; Ye, Runyu; Li, Xinran; Gou, Qiling; Zhang, Zhipeng; Shi, Rufeng; Meng, Qingtao; Zhuoma, Zewong; Zhang, Hengyu; Chen, Xiaoping
Abstract: Twenty‐four‐hour urine collection is the gold standard method for the evaluation of salt intake, but it is often impractical in large‐scale investigations, especially in resource‐poor areas. Methods for the estimation of 24‐hour urinary sodium excretion (USE) using a spot urine sample have been established, but have not been validated in Chinese Tibetans. Therefore, the authors aimed to evaluate the Kawasaki, Tanaka, and the International Cooperative Study on Salt, Other Factors, and Blood Pressure (INTERSALT) formulas for the prediction of 24‐hour USE in Chinese Tibetan adults. The authors analyzed the bias, correlation, agreements between estimated values and measured values, and the relative and absolute differences and misclassification at the individual level for the three methods in 323 Tibetan participants from the Ganzi Tibetan Autonomous Prefecture of Sichuan Province, China. The mean biases between the measured values and the estimated 24‐hour USE using the Kawasaki, Tanaka, and INTERSALT methods were 5.4 mmol/day (95% confidence interval [CI]: 0.8–10.1 mmol/day), −40.8 mmol/day (95% CI: −44.6 to −36.9 mmol/day), and −57.1 mmol/day (95% CI: −61.9 to −52.4 mmol/day), respectively. The Pearson correlation coefficients for the relationships between the measured values and the estimated 24‐hour USE were 0.43 (Kawasaki), 0.38 (Tanaka), and 0.27 (INTERSALT), respectively (all p < .01). The intraclass correlation coefficients showed similar patterns to the correlation data: 0.47 for Kawasaki, 0.40 for Tanaka, and 0.27 for INTERSALT (all p < .01). The upper and lower limits of agreement between the measured values and the estimated 24‐hour USE were −92.6 and 81.8 mmol/day for the Kawasaki method, −28.5 and 110.0 mmol/day for the Tanaka method, and −28.4 and 142.7 mmol/day for the INTERSALT method. Compared with the other two methods, the percentage of individuals that were misclassified by using the Kawasaki method was 48.2%, while those for the Tanaka and INTERSAL methods was 72.1% and 75.5%, respectively. However, when an individual's salt intake was higher than 12.8 g/day, the misclassification rates of the Kawasaki, Tanaka, and INTERSALT methods were 20%, 90%, and 97.5%, respectively. Thus, the authors found that the Kawasaki equation may have performed better than the other equations at Chinese Tibetan population level assessment, but none of these equations are suitable for use or perform well at the individual level. A more accurate method of using a spot urine sample to evaluate individual 24‐hour USE for Tibetans is needed.